Previous in Relation and Functions Next in Relation and Functions | ||
Question Number 124065 by Bird last updated on 30/Nov/20 | ||
$${determine}\:{tbe}\:{sewuence}\:{u}_{{n}} \\ $$ $${wich}\:{verify}\:{u}_{{n}} +{u}_{{n}+\mathrm{1}} =\frac{\left(−\mathrm{1}\right)^{{n}} }{\:\sqrt{{n}}} \\ $$ $${n}>\mathrm{0} \\ $$ | ||
Answered by mindispower last updated on 30/Nov/20 | ||
$$\left(−\mathrm{1}\right)^{{n}} {u}_{{n}} +\left(−\mathrm{1}\right)^{{n}} {u}_{{n}+\mathrm{1}} =\frac{\mathrm{1}}{\:\sqrt{{n}}} \\ $$ $$\underset{{k}=\mathrm{1}} {\overset{{n}} {\sum}}\left(−\mathrm{1}\right)^{{k}} {u}_{{k}} +\left(−\mathrm{1}\right)^{{k}} {u}_{{k}+\mathrm{1}} =\underset{{k}=\mathrm{1}} {\overset{{n}} {\sum}}\frac{\mathrm{1}}{\:\sqrt{{k}}} \\ $$ $$\left(−\mathrm{1}\right)^{{n}} {u}_{{n}+\mathrm{1}} −{u}_{\mathrm{1}} =\underset{{k}=\mathrm{1}} {\overset{{n}} {\sum}}\frac{\mathrm{1}}{\:\sqrt{{k}}} \\ $$ $${u}_{{n}} =\left(−\mathrm{1}\right)^{{n}−\mathrm{1}} {u}_{\mathrm{1}} +\left(−\mathrm{1}\right)^{{n}−\mathrm{1}} \underset{{k}\leqslant{n}−\mathrm{1}} {\sum}\frac{\mathrm{1}}{\:\sqrt{{k}}},\forall{n}\geqslant\mathrm{2} \\ $$ $$ \\ $$ | ||